Alternative low-cost precipitation kit for assessing irrigation systems - Filgueiras, Roberto; Cunha, Fernando França da; Venancio, Luan Peroni; Althoff, Daniel; Santos, Robson Argolo do; Santos, Jannaylton Éverton Oliveira; Alencar, Carlos Augusto Brasileiro de (Semina: Ciências Agrárias, 2020)
Irrigation systems must be assessed periodically to verify equipment quality and the need for adjustments. For this, precipitation test kits are necessary. However, commercially available kits have as their main disadvantage the high cost. Therefore, this study aimed to develop an alternative low-cost precipitation kit and verify its efficiency compared to an available commercial brand. The validation test was carried out at the Laboratory of Hydraulics of the Federal University of Viçosa (UFV) using a conventional sprinkler system organized in a quadrangular arrangement. Water collections were carried out within two hours using a grid of plastic collectors spaced at 3 Ã— 3 m and installed at 0.7 m above the ground. The coefficient of determination (R2), uniformity coefficients, application efficiency, and thematic maps of the spatial variability of the applied irrigation depth were compared between kits and used for the validation of measurements. The results showed a high agreement between the developed (GESAI) and a commercial kit (Trademark) (R2 = 0.9849), and a high spatial agreement between the collected water depths. Therefore, the GESAI kit is a low-cost alternative for the assessment of irrigation systems.